THE PHILOSOPHICAL CONTENTS OF DIWAN LUGHAT AL-TURK - Tasdelen, Vefa (HITIT UNIV, 2020)
Philosophy is a work of mind which is produced in language. The power of expression regarding being, mankind, society, morality, and value manifests the philosophical potential of a language as well. The potential of the language is the potential of philosophy and the potential of philosophy is the potential of the language. Diwan Lughat al-Turk is one of the oldest and the most important texts of Turkish culture. This work that is written to teach Turkish to foreigners, is not a work of dictionary in a simplistic sense, it has a quality of an anthology which presents the samples from the structure of the language of its own period such as poetry, proverb, and story according to the requirement of the language teaching that is embodying and exemplary. It is one of the works that has a quality of exhibiting the philosophical potential of Turkish, the possibility to conceive and articulate the being in scope of the riddle of human being, God and universe; for the first time as in the most advanced level. This article aims to deal with the philosophical content in the text. In this article words, idioms, proverbs, poems, stories, and sample sentences will be examined in terms of their philosophical contents and connotations. This accumulation, will take place in order to reflect the holistic perspective of philosophy within the frame of: (1) conception of being, (2) conception of knowledge, (3) conception of human, (4) ethical and aesthetic values.
Keywords: Philosophy; Diwan Lughat al-Turk; Mahmud al-Kasrari; Being; Knowledge; Ethics; Aesthetics; Religion